2013
DOI: 10.1242/jcs.jcs124404
|View full text |Cite
|
Sign up to set email alerts
|

Protein with tau-like repeats regulates neuronal integrity and lifespan inC. elegans

Abstract: SummaryProtein with tau-like repeats (PTL-1) is the sole Caenorhabditis elegans homolog of tau and MAP2, which are members of the mammalian family of microtubule-associated proteins (MAPs). In mammalian neurons, tau and MAP2 are segregated, with tau being mainly localised to the axon and MAP2 mainly to the dendrite. In particular, tau plays a crucial role in pathology, as elevated levels lead to the formation of tau aggregates in many neurodegenerative conditions including Alzheimer's disease. We used PTL-1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 63 publications
(103 reference statements)
3
74
1
Order By: Relevance
“…We visualised GABAergic neuron branching on days 1, 5, 7 and 9 of adulthood using the P unc-47 :: gfp(oxIs12) reporter. As noted previously3457, GABAergic neurons in young animals do not show branching in the dorsally-projecting commissures, which are often branched in older adults (Figure 3a). We found that re-expressing PTL-1 in all neurons in the ptl-1 null mutant background completely rescued premature neuronal ageing observed in ptl-1(ok621) mutant animals (Figure 3b).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…We visualised GABAergic neuron branching on days 1, 5, 7 and 9 of adulthood using the P unc-47 :: gfp(oxIs12) reporter. As noted previously3457, GABAergic neurons in young animals do not show branching in the dorsally-projecting commissures, which are often branched in older adults (Figure 3a). We found that re-expressing PTL-1 in all neurons in the ptl-1 null mutant background completely rescued premature neuronal ageing observed in ptl-1(ok621) mutant animals (Figure 3b).…”
Section: Resultssupporting
confidence: 79%
“…Specifically, 70% of TRN SID-1 animals fed ptl-1 RNAi bacteria displayed cell body branching at day 7 compared with 47% in the EV RNAi control, and 53% of ptl-1 RNAi-fed animals displayed axon blebbing compared with 30% of the control population (Figure 4ai). In addition, we observed that TRN SID-1 animals displayed a relatively high frequency of axon branching (Figure 4aii), which is normally only present in late stage (day 10) adult animals57. TRN SID-1 animals fed with both control and ptl-1 RNAi treatments showed considerably higher levels of axon branching in the anterior TRNs compared with wild-type controls, although transgenic animals fed ptl-1 bacteria displayed a higher incidence of this phenotype compared with EV treatments (Figure 4ai).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Tau belongs to the family of microtubule-associated proteins (MAPs), with tau being the prototypical axonal and MAP2 the prototypical dendritic family member [2]. MAPs have a central role in neuronal integrity [3]. While tau has a major function in the axon, early on it was recognized that this protein has also important physiological functions in other compartments, such as the dendrite, where low concentrations of tau facilitate the targeting of the tyrosine-directed kinase Fyn to the dendritic spines [4].…”
mentioning
confidence: 99%
“…Mechanistically it has been shown that the mutations reduce microtubule binding and facilitate Tau polymerization [109,110] elegans where the Tau homologue Ptl-1 has been shown to regulate structural neuronal integrity [112,113].…”
Section: Introductionmentioning
confidence: 99%